MONITORING THE THERAPEUTIC EFFECTS OF DECORIN IN HYDROCEPHALUS. Issue 12 (15th November 2016) - Aojula, Anuriti; Botfield, Hannah; McAllister, James Patterson; Gonzalez, Ana Maria; Abdullah, Osama; Logan, Ann; Sinclair, Alexandra
Abstract : Background: The use of diffusion tensor imaging (DTI) to examine Decorin's ability to prevent cerebral cytopathology in communicating hydrocephalus is yet to be fully investigated. Hence, this study aimed to determine whether Decorin treatment influences alterations in DTI parameters and cytopathology in an experimental model of the disease. Method: Accordingly, communicating hydrocephalus was induced by injecting Kaolin into the basal cisterns in 3-week old rats followed immediately by 14 days of continuous intraventricular delivery of either human recombinant Decorin (n=5) or vehicle (n=6). At 14-days post-kaolin, just prior to sacrifice, DTI was conducted. Myelin integrity (myelin basic protein), gliosis (glial fibrillary acidic protein, GFAP) and aquaporin-4 levels were evaluated by immunohistochemistry in the same seven cerebral structures analysed by DTI. Results: Decorin significantly decreased myelin damage in the caudal internal capsule and prevented caudal periventricular white matter oedema and astrogliosis. Furthermore, Decorin treatment prevented an increase in caudal periventricular white matter mean diffusivity (p=0.032) as well as caudal corpus callosum axial diffusivity (p=0.004) and radial diffusivity (p=0.034). Furthermore, DTI parameters correlated primarily with periventricular white matter GFAP and aquaporin-4 levels. Conclusion: Overall, these findings suggest that Decorin has the therapeutic potential to reduce white matter cytopathology in communicating hydrocephalus.